Comparability and Objectivity of Exit Value Accounting: A Comment. - Hartman, Bart P.; Zaunbrecher, H. C. (The Accounting Review, 1976)
Abstract This article presents a commentary over an article by James E. Parker, previously published in the July 1975 issue, related to comparability and objectivity of exit value accounting. Parker reported the results of an experiment designed to assess the comparability and objectivity of exit values relative to historical cost values. In the experiment, twenty-six exit values obtained for one 6-year-old calculator were compared with the adjusted historical-cost-based values for twenty-six different calculators. The author of this article comments on the adequacy of the experimental design and suggests alternative procedures which may have validated further the experimental results. According to the author, Parker did have a valid test of objectivity for exit values, but not for historical cost values. In effect, Parker ended up with a valid objectivity measure for exit value and a valid comparability measure for historical cost. By using invalid measures of objectivity for historical cost and invalid measures of comparability for exit value, bias was introduced to both the objectivity and comparability analyses.